Catalyst Free Silicone Sealants That Cure Underwater. (9th April 2020) - Bui, Robert; Brook, Michael A.
Abstract: Silicone sealants and adhesives are widely used to prevent the ingress of water. However, silicones must normally be cured in air, as excess water inhibits or prevents cure from occurring. It is reported that aqueous solutions of the aliphatic aldehydes glutaraldehyde, glyoxal or, particularly, formaldehyde rapidly react without catalysts with a variety of aminopropyl‐modified silicone polymers to give silicone elastomers, even underwater. These products, whose properties are readily tailored by controlling the density of amino groups in the starting materials, may be 3D printed, or used both as adhesives and sealants in air or water. Abstract : Aqueous solutions of the small aldehydes glutaraldehyde, glyoxal, and especially formaldehyde, react rapidly with aminopropylsilicones to create silicone elastomers in air or under water, that can act as sealants or adhesives, including in 3D printing applications.